2020
DOI: 10.1038/s41598-020-64858-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA can act as a biodiversity barometer of anthropogenic pressures in coastal ecosystems

Abstract: Loss of biodiversity from lower to upper trophic levels reduces overall productivity and stability of coastal ecosystems in our oceans, but rarely are these changes documented across both time and space. The characterisation of environmental DNA (eDNA) from sediment and seawater using metabarcoding offers a powerful molecular lens to observe marine biota and provides a series of ‘snapshots’ across a broad spectrum of eukaryotic organisms. Using these next-generation tools and downstream analytical innovations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 89 publications
3
73
0
Order By: Relevance
“…The development of eDNA as a reliable method to monitor biodiversity and evaluate anthropogenic impacts is crucial because important changes in biodiversity might currently occur under our radar [39,57]. Depending on the organisms of interest, eDNA can be used to sample whole eukaryote assemblages [58] or more specific taxonomic groups ranging from sponges and corals [59] to larger taxa such as sharks [30]. In our case, we potentially missed some native and common species in the Mediterranean Sea since the teleo marker cannot distinguish the wrasses Symphodus rostratus, S. cinnereus, S. mediterraneus, and S. roissali from each other, or Labrus merula from L. viridis, as well as the rarer pipefishes Syngnathus abaster and S. sp cfr taenionotus.…”
Section: (B) Potential and Limitations Of Edna Metabarcodingmentioning
confidence: 99%
“…The development of eDNA as a reliable method to monitor biodiversity and evaluate anthropogenic impacts is crucial because important changes in biodiversity might currently occur under our radar [39,57]. Depending on the organisms of interest, eDNA can be used to sample whole eukaryote assemblages [58] or more specific taxonomic groups ranging from sponges and corals [59] to larger taxa such as sharks [30]. In our case, we potentially missed some native and common species in the Mediterranean Sea since the teleo marker cannot distinguish the wrasses Symphodus rostratus, S. cinnereus, S. mediterraneus, and S. roissali from each other, or Labrus merula from L. viridis, as well as the rarer pipefishes Syngnathus abaster and S. sp cfr taenionotus.…”
Section: (B) Potential and Limitations Of Edna Metabarcodingmentioning
confidence: 99%
“…Additionally, Buxton et al (2018) found, when examining eDNA of the great crested newt (Triturus cristatus) in aquatic and sediment samples, that detection varied throughout the year based on habitat suitability and species ecology. Work has also been done in ocean systems with studies ranging from examining shark diversity response to anthropogenic disturbance to understanding how anthropogenic activities such as oil spills and development impact micro and macro coastal communities (Bakker et al, 2017;Xie et al, 2018;DiBattista et al, 2020). Sun et al (2019) used eDNA metabarcoding to understand Dipteria and other organism populations in human caused roadside stormwater ponds.…”
Section: Introductionmentioning
confidence: 99%
“…As the name indicates, eDNA is genetic material that has been deposited into the environment via numerous sources, such as skin, feces, urine, larvae, and gametes. DNA extracted directly from environmental samples (e.g., filtered seawater, soil, and sand) can be sequenced to identify source organisms occupying the proximate area of the collected sample (Laramie et al, 2015;Minamoto et al, 2016;Hinlo et al, 2017;Dibattista et al, 2020). Accordingly, eDNA-based investigations have proven to be as valuable as traditional survey methods that require capture and subsampling of target organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, eDNA methods are a less-intrusive approach to studying invasive or declining species (Zhou et al, 2013;Bucklin et al, 2016;Holman et al, 2019;Nelson-Chorney et al, 2019), documenting the distribution of difficult to sample taxa (Parsons et al, 2018), and estimating relative seasonal biomass of target species (Takasu et al, 2019;Stoeckle et al, 2020). Marine-derived eDNA has also been likened to a "barometer of disturbance" with respect to its potential to assess anthropogenic effects on ecosystems (Dibattista et al, 2020).…”
Section: Introductionmentioning
confidence: 99%